From FeO reduction to percolation and outflow of iron thermal evolution of chondrite parent bodies - Bérczi Szaniszló; Lukács Béla; Holba Ágnes; Kiss A.; Papp É. (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1998)
Some high petrologic class (6 & 7) members of the NIPR Antarctic Meteorite collection show signals indicating iron outflow. Meteorites are endpoints of heat-driven evolutions at various temperatures, and probably higher petrologic class corresponds to higher heat impact. At high enough temperature one expects liquidification of iron, resulting in iron loss from the texture. Compositional data suggest that the iron loss starts at petrologic class 6; at classes 6 and 7 of any chondrite type metallic iron (and maybe FeS) is less than for 1-5. So petrologic class 6 exhibit a stage just before iron loss by flowing out: a stage of starting percolation of Fe. Percolation is a stage of phase transitions, when all the domains of the growing new phase have become interconnected but still the old phase exists. In this phase molten iron can form interconnected patches. This is the last stage before iron loss: if the percolated domain reaches a fault line, then Fe can start to flow out. This stage of thermal evolution is the link between chondrites and some achondrites, because at this stage the temperature is already high enough, so diffusion is so strong that chondrules start to be obliterated. In order to see if this scheme is viable, it is necessary to give an overview of heat-induced evolution; afterwards we give measurements for the differences of iron grain distribution throughout the type LL, according to PC's.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok